Electromyostimulation to fight atrophy and to build muscle: facts and numbers. Issue 4 (20th July 2018) - Adams, Volker
Abstract: In recent years, electrical myostimulation (EMS) is becoming more and more popular to increase muscle function and muscle weight. Especially it is applied in healthy individual after injury to rebuild muscle mass and in severely atrophic patients who are not able or willing to perform conventional exercise training programs. Studies in experimental models as well as in human subjects confirmed that EMS can increase muscle mass by around 1% and improve muscle function by around 10–15% after 5–6 weeks of treatment. Despite a severe increase in circulating creatine kinase during the first session, EMS can be regarded as a safe therapeutic intervention. At the molecular level, EMS improves the anabolic/catabolic balance and stimulates the regenerative capacity of satellite cells. EMS intensity should be as high as individually tolerated, and a minimum of three sessions per week [large pulses (between 300–450 μs), high frequency (50–100 Hz in young and around 30 Hz in older individuals)] for at least 5–6 weeks should be performed. EMS improved functional performances more effectively than voluntary training and counteracted fast type muscle fibre atrophy, typically associated with sarcopenia. The effect of superimposing EMS on conventional exercise training to achieve more muscle mass and better function is still discussed controversially. Nevertheless, EMS should not be regarded as a replacement of exercise training per se, since the beneficial effect of exercise training is not just relying on building muscle mass but it also exerts positive effects on endothelial, myocardial, and cognitive function.